Congenital Malalignment of the Great Toenails with Secondary Retronychia: A Tale of Twin Toenails - Forman, Carrie A.; Desir, Noelle; Ong, Michael M.; Lipner, Shari R. (Case reports in dermatology, 2025)
Introduction: Congenital malalignment of the great toenail (CMGT) is characterized by deviation of the nail plate due to rotation of the nail matrix. CMGT may be complicated by secondary retronychia. Case Presentation: We report a case of twin 14-year-old females who presented with CMGT with secondary retronychia with no clear inciting event. Physical examination demonstrated lateral deviation of the great toenails with yellowed, thickened, and layered nail plates, consistent with a diagnosis of CMGT with secondary retronychia. The patients were advised to make relevant lifestyle changes and treated with clobetasol proprionate 0.05% ointment to use on all toenails daily for 3 months, with 1 week off per month, under occlusion. Conclusion: We hypothesize that both genetic and environmental factors likely contributed to the development of CMGT with secondary retronychia in these twins. Increased awareness and recognition of this underdiagnosed condition, particularly in the pediatric population, is important for timely and effective management.